1995
DOI: 10.1017/s0033291700028099
|View full text |Cite
|
Sign up to set email alerts
|

Autism as a strongly genetic disorder: evidence from a British twin study

Abstract: SynopsisTwo previous epidemiological studies of autistic twins suggested that autism was predominantly genetically determined, although the findings with regard to a broader phenotype of cognitive, and possibly social, abnormalities were contradictory. Obstetric and perinatal hazards were also invoked as environmentally determined aetiological factors. The first British twin sample has been re-examined and a second total population sample of autistic twins recruited. In the combined sample 60% of monozygotic (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

44
1,339
4
34

Year Published

2006
2006
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 2,155 publications
(1,453 citation statements)
references
References 42 publications
44
1,339
4
34
Order By: Relevance
“…However, twin and family data have indicated that the genetic liability to autism confers a risk for a broader range of autistic-like impairments. 31,32 Our findings provide more support for this conclusion and add further justification for the inclusion of these broader phenotypic variants in molecular genetic studies. Our findings also suggest that some of the variability in phenotypic expression within the autistic spectrum is not due to genetic variation at this locus.…”
supporting
confidence: 70%
“…However, twin and family data have indicated that the genetic liability to autism confers a risk for a broader range of autistic-like impairments. 31,32 Our findings provide more support for this conclusion and add further justification for the inclusion of these broader phenotypic variants in molecular genetic studies. Our findings also suggest that some of the variability in phenotypic expression within the autistic spectrum is not due to genetic variation at this locus.…”
supporting
confidence: 70%
“…No twin study on AS or PDD-nos has been performed to date. A re-analysis of one twin study 82 with regard to the BAP, which was conceptualized for two areas, communication impairment and social dysfunction, did shown far higher rates of the BAP in discordant MZ than in discordant DZ pairs. 91 Among the MZ co-twin, communication impairment and social dysfunction frequently cooccurred together, whereas restricted, stereotyped or repetitive behaviours were never seen in isolation, and were present in only one third of the individuals with BAP.…”
Section: Formal Genetics and Patterns Of Inheritancementioning
confidence: 98%
“…[82][83][84][85] It has been discussed that twinning in itself might be a risk factor for the development of autism. 86,87 However, three large-scale epidemiological studies have refuted this idea.…”
Section: Formal Genetics and Patterns Of Inheritancementioning
confidence: 99%
“…Monozygotic (MZ) twins are 69-95% concordant, 2,3 whereas dizygotic (DZ) twins are 0-24% concordant. [2][3][4][5][6] When a broader phenotype (BPH) is used, concordance increases for both MZ (88-91%) and DZ (9-30%) twins. 2,5,6 Reported sib risks are consistent with DZ twin concordance rates ranging from 2.8 to 7.0% whereas rates in control families are much lower.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5][6] When a broader phenotype (BPH) is used, concordance increases for both MZ (88-91%) and DZ (9-30%) twins. 2,5,6 Reported sib risks are consistent with DZ twin concordance rates ranging from 2.8 to 7.0% whereas rates in control families are much lower. [7][8][9] In contrast, the rate of autism in relatives more distant than sibs is extremely low.…”
Section: Introductionmentioning
confidence: 99%